Manufacture and Application of Compost Fertilizer from Dried Leaves: Array - Cindera Nur Hayati; Ike Hidhayatul Sholehah; Ayu Sulistiani; Agung Setyawan (Lembaga Citra Pustaka, 2022)
Organic waste comes from organic materials that can be decomposed by microorganisms (biodegradable). Handling organic waste and dry leaves concerning the 3R method is to recycle so that it becomes a product that can be useful and even gain added value, namely into compost. Making compost can also be given additional materials from probiotic microorganisms such as EM4. EM4 helps improve soil structure and texture, supplying nutrients and inhibiting the growth of pests, diseases, and others (Nurkhasanah et al., 2021). This composting activity includes collecting and sorting composting materials, preparing composting tools and materials, and composting practices. Adding organic matter to compost is expected to improve soil physical properties, especially soil permeability and aeration, increase water retention and erosion resistance, and reduce surface runoff.